Blood on the sea : American destroyers lost in World War II - Parkin, Robert Sinclair (New York : Sarpedon, 1995)
Seventy-one United States Navy destroyers were lost in the Second World War. This book, in describing each battle, takes the reader on a breathtaking tour of American military action, on a multitude of fronts and on both sides of the globe.
Includes bibliographical references (pages 347-348) and index.
Keywords: United States. -- Navy -- History -- World War, 1939-1945.; United States. -- Navy; 1900-1999; World War, 1939-1945 -- Naval operations, American; Destroyers (Warships) -- United States -- History -- 20th century; Shipwrecks -- History -- 20th century; Guerre mondiale, 1939-1945; Destroyers -- x; Naufrages -- Histoire; Destroyers (Warships); Military operations, Naval -- American; Shipwrecks; World War II; United States -- History, Naval -- 20th century; x; United States; History; Naval history